2006
DOI: 10.1212/wnl.67.7_suppl_2.s24
|View full text |Cite
|
Sign up to set email alerts
|

Symptom relief in Parkinson disease by safinamide

Abstract: In an open pilot study, doses of safinamide (100, 150, and 200 mg once a day, higher than previously tested) were administered to 13 parkinsonian patients along with a stable dose of dopamine (DA) agonist, causing a significant progressive improvement in motor performance as evaluated by the Unified Parkinson Disease Rating Scale (UPDRS) part III over an 8-week period (4.2 points; P < 0.001). In association with levodopa, the same doses of safinamide in another group of patients (N = 11) induced a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 14 publications
3
40
0
Order By: Relevance
“…Safinamide is a highly selective and reversible MAO B inhibitor that also appears to have the capability of blocking voltage-dependent sodium and calcium channels and therefore inhibiting glutamate release. [137][138][139] Pilot studies have demonstrated improvement in nonfluctuating and fluctuating PD. 138 Finally, changes in technology may allow the development of an easier and safer way to provide continuous infusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Safinamide is a highly selective and reversible MAO B inhibitor that also appears to have the capability of blocking voltage-dependent sodium and calcium channels and therefore inhibiting glutamate release. [137][138][139] Pilot studies have demonstrated improvement in nonfluctuating and fluctuating PD. 138 Finally, changes in technology may allow the development of an easier and safer way to provide continuous infusions.…”
Section: Discussionmentioning
confidence: 99%
“…[137][138][139] Pilot studies have demonstrated improvement in nonfluctuating and fluctuating PD. 138 Finally, changes in technology may allow the development of an easier and safer way to provide continuous infusions. Subcutaneous apomorphine infusions have been used successfully in the United Kingdom for the treatment of motor fluctuations, but there have been significant technical difficulties and associated cutaneous adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, doses over 100 mg/day have not conferred significant benefit for early or late PD study primary end points [21]. It is a once per day oral dose with no need for dose readjustments once it is established.…”
Section: Pharmacology Of Safinamidementioning
confidence: 99%
“…Safinamide has no Catechol-O-methyltransferase (COMT) activity [21] and as mentioned its MAOB activity is saturated at doses below those that produce clinical motor improvements. Although safinamide has known effects on glutamate, ion channels and free radicals, none of these actions sufficiently explain sustained peripheral dopamine levels with safinamide.…”
Section: Pharmacology Of Safinamidementioning
confidence: 99%
“…In several experimental in vitro and in vivo models, safinamide exerts neurorescuing and neuroprotective effects. In a small pilot study involving 13 PD patients receiving a high dose of safinamide, a symptomatic motor benefit was detected [31]. A phase III, double-blind, placebo-controlled study is ongoing to investigate the efficacy and safety of higher doses of safinamide (50-200 mg/day) as add-on therapy in patients with early PD.…”
Section: Safinamidementioning
confidence: 99%